Pemahaman dan Minat Konsumen dalam Menggunakan Quick Response Indonesian Standard Sebagai Alat Pembayaran Digital di Daerah Kecamatan Cinere - Reza Imani Syawal; Baskoro Harwindito; Reni Sulistiyowati (Politeknik Sahid, 2021)
This study aims to measure how well consumers understand and interest in QRIS as a digital payment instrument. Consumer understanding of QRIS can influence its use as a digital means of payment. The higher the consumer's understanding of how to use QRIS and its benefits, the more likely they are to be interested in using it. The research method used in this study is quantitative analysis, which collects data in the form of numbers or quantitative measures and then analyzes them systematically using statistical techniques to draw reliable conclusions. The data collection technique used was a questionnaire, while the data analysis technique used was descriptive statistics using a percentage formula. The results of this study indicate that the majority of respondents agree with the use of QRIS in digital transactions, which is found through percentage calculations.